Subterranean carbon flows from source to stygofauna: a case study on the atyid shrimp Stygiocaris stylifera (Holthuis, 1960) from Barrow Island (WA). Issue 3 (4th May 2022) - Saccò, Mattia; Humphreys, William F.; Stevens, Nicholas; Jones, Matthew R.; Taukulis, Fiona; Thomas, Erin; Blyth, Alison J.
ABSTRACT: Groundwater biota are crucial for the ecological functioning of subterranean ecosystems. However, while knowledge of the taxonomic diversity of groundwater invertebrates (stygofauna) is increasing, functional ecological information is still limited. Here, we investigate seldom empirically tested assumptions around stygofaunal trophic plasticity in coping with oligotrophic habitats. We focus on Barrow Island (Western Australia), an ideal natural laboratory due to the occurrence of natural oil seeps in association with aquifers. The trophic position and food source use of the endemic atyid shrimp Stygiocaris stylifera (Holthuis, 1960) were assessed via δ 13 C and δ 15 N stable isotope analysis (SIA). Background information on the environmental conditions was gathered through hydrochemical data and δ 13 C SIA combined with 14 C data from dissolved inorganic/organic carbon and particulate organic carbon from groundwater samples. Our results indicate carbon enrichment in proximity to the natural oil seepage coupled with changes in trophic positions of S. stylifera from higher consumers/predators to biofilm grazers/decomposers. These results are consistent with an increased involvement of hydrocarbon seeps and associated microbial communities in the carbon flows and confirm potential for the trophic flexibility in stygofauna. Further investigations involving other trophic groups will help elucidate the functioning of the ecosystems at a community level.